Comparative study between crossbred and caucasians individuals using Ricketts cefalometric analysis - Menéndez Méndez, Leoncio (2009)
This study aimed to compare the sample mixed with Caucasian Ricketts cephalometric radiographs and determine if there are significant differences between the values found in our sample and standardized measures of Caucasians used as a standard in our study. The population was based on adolescent women’s secondary school level “Rosa de Santa Maria” Breña district, between 11 to 16 years of age. Which was selected a sample of 32 students, with characteristic patterns of racial mixing as peruvian anthropology. We considered Extraoral and intraoral characteristics for the selection of the sample, use the cephalometric x-ray equipment and a SRL camera for a photographic record of the facial features. The results were processed using SPSS v.17, expressing the results under descriptive measures and using Z statistical test to find differences at 95 % confidence. It was concluded that these differences become more evident in the following values: aesthetic line “E” 0.5 mm, inter-incisor angle 124 degrees, point “A” to N-Pg line up to 4 mm, length anterior cranial base 56 mm, confirming the hypothesis that if there are significant differences between the Peruvian mestizo sample with the Caucasian group Ricketts.